Legal Protection For Creditors In Credit Agreements With Guaranteed Dependent Rights From The Perspective of Law No. 4 of 2023 - Septian Uky Kriscahya; Suwardi Suwardi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Creditors are parties who have receivables based on agreements or legal provisions that can be collected through legal channels. In the practice of lending, collateral is very important to provide legal certainty and a sense of security for both parties, both creditors and debtors. This study discusses two main problem formulations, namely the position of the guarantee of dependents against creditors when the debtor defaults, and the form of legal protection for creditors if the right of dependency cannot be executed. The method used is normative juridical research that examines the applicable positive legal provisions. The results of the study show that if the debtor defaults, the creditor has the right to execute the collateral object through sale to cover his receivables. However, under certain conditions the right of dependency cannot be executed, so a legal mechanism is needed that provides protection to creditors. This protection is regulated in Law Number 4 of 1996 concerning Dependent Rights, especially in the articles that regulate the definition of dependent rights, the execution process, and the principle of droit de suite which guarantees the rights of creditors to the collateral object even if they change hands. Thus, the legal system of dependent rights is an important instrument in ensuring certainty and legal protection for creditors.